Does Self-Efficacy and Emotional Control Protect Hospital Staff From COVID-19 Anxiety and PTSD Symptoms? Psychological Functioning of Hospital Staff After the Announcement of COVID-19 Coronavirus Pandemic - Bidzan, Monika; Bidzan-Bluma, Ilona; Szulman-Wardal, Aleksandra; Stueck, Marcus; Bidzan, Mariola (Frontiers in Psychology, 2020)
Objectives: The aim of this study was to assess COVID-19 anxiety and PTSD symptoms in the hospital staff, as well as to identify protective factors of COVID-19 anxiety once the coronavirus pandemic was announced in Poland. Methods: 90 healthcare workers from the hospital in Poland completed validated self-report questionnaires assessing self-efficacy, emotional control, and PTSD symptoms; a questionnaire assessing COVID-19 anxiety, and a socio-demographic questionnaire. A multiple linear regression was conducted to assess the effects of gender, being directly vs indirectly exposed to patients, and general self-efficacy on COVID-19 anxiety. Results: The analysis showed that females (β = -.271, p < .01) healthcare professionals indirectly exposed to patients (β = -.336, p < .01), and those who reported lower levels of general self-efficacy (β = -.295, p < .01) have a stronger tendency to experience COVID-19 anxiety [R2 = .301, F(3, 89) = 12.34, p < .01]. Conclusions: The findings show the importance of Self-Efficacy for dealing with COVID-19 anxiety. The internal coping strategies should be introduced to healthcare workers.